Bilingual Approach: The Role of Flashcards in Teaching Vocabulary to Young Learners - Erniwati Erniwati; Sudarkam R Mertosono; Muhammad Arid; Afrillia Anggreni (Universitas Muhammadiyah Makassar, 2021)
This paper discusses teaching approach and media in English as a foreign language (EFL) classroom. It brings to lights vocabulary teaching, bilingual approach and using flashcards in the teaching of vocabulary to young learners. As teaching vocabulary can take place from very early stage to a high level of learning, its introduction needs to be managed in such a way using an appropriate approach along with utilizing particular media, such as flashcards, that the learners can enjoy the teaching process. This is based on the consideration that not all teaching media fit in the context of vocabulary teaching through bilingual approach. For this reason, it is important that teachers of English whose concern is how young learners learn vocabulary adopt appropriate teaching media on their behalf. Once the learners feel secured and confortable with the media used, it is guaranteed that they can learn as many words as possible and, thus, the desired outcome of the learning can be projected to occur. This article emphasizes the issue of bringing together bilingual approach and flahcards together in the teaching of vocabulary to young learners.